2021
DOI: 10.1021/acsaem.0c02909
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of AgGaSe2 as a Wide Gap Solar Cell Absorber

Abstract: The compound AgGaSe 2 has received limited attention as a potential wide gap solar cell material for tandem applications, despite its suitable band gap. This study aims to investigate the potential of this material by deposition of thin films by co-evaporation and production of solar cell devices. Since AgGaSe 2 has a very low tolerance to off-stoichiometry, reference materials of possible secondary phases in the Ag 2 Se−Ga 2 Se 3 system were also produced. Based on these samples, it was concluded that X-ray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…This phase is not very conductive but has a low E g and is likely defect rich. [43] Summarizing all findings, it can be concluded that Ag alloying reduces recombination at the buffer interface in chalcopyrite solar cells with GGI > 0.5. [24] This allows producing such low V OC deficits with CdS as only possible for pure CIGS when using alternative buffers (see Figure S4, Supporting Information).…”
Section: General Considerations Regarding Wide-gap Acigsmentioning
confidence: 76%
See 4 more Smart Citations
“…This phase is not very conductive but has a low E g and is likely defect rich. [43] Summarizing all findings, it can be concluded that Ag alloying reduces recombination at the buffer interface in chalcopyrite solar cells with GGI > 0.5. [24] This allows producing such low V OC deficits with CdS as only possible for pure CIGS when using alternative buffers (see Figure S4, Supporting Information).…”
Section: General Considerations Regarding Wide-gap Acigsmentioning
confidence: 76%
“…Obviously, the OVC surface fraction decreases toward stoichiometric composition until eventually no OVCs can be measured for [I]/[III] > 0.97. For larger [I]/[III] values, the I-rich Ag 9 GaSe 6 phase starts to segregate, [28,43] possibly accompanied by a minor fraction of (Ag y ,Cu 1Ày ) 2Àx Se. It is unclear if for common absorber deposition routines, a phase-pure 1:1:2 chalcopyrite film can be formed at perfect integral stoichiometry or if minor OVC and Ag 9 GaSe 6 segregations coexist.…”
Section: Width Of the Chalcopyrite 1:1:2 Single-phase Regionmentioning
confidence: 99%
See 3 more Smart Citations